The ethics of lottery advertising: Issues and evidence - Stearns, James M. (Journal of business ethics, 1995)
After a discussion of the evolution and criticisms of state run lotteries, this article examines the ethics of lottery advertising. A discussion of the appeals used by lottery advertisers is followed by evidence concerning the impact of expected value information on lottery purchase intentions. Findings point toward less emphasis on the lottery as a solution to financial and job problems and more emphasis on information about the actual value of a lottery bet. Using accepted standards from the marketing literature, lottery advertising is found to be deceptive.